Teaching translation programs, courses, pedagogies - Venuti, Lawrence (Routledge, Taylor & Francis Group, 2017)
Over the past half century, translation studies has emerged decisively as an academic field around the world, and in recent years the number of academic institutions offering instruction in translation has risen along with an increased demand for translators, interpreters and translator trainers. Teaching Translation isthe most comprehensive and theoretically informed overview of current translation teaching. Contributions from leading figures in translation studies are preceded by a substantial introduction by Lawrence Venuti, in which he presents a view of translation as the ultimate humanistic task -- an interpretive act that varies the form, meaning, and effect of the source text. 26 incisive chapters are divided into four parts, covering certificate and degree programs ; teaching translation practices ; studying translation theory, history, and practice ; surveys of translation pedagogies and key textbooks. The chapters describe long-standing programs and courses in the US, Canada, the UK, and Spain, and each one presents an exemplary model for teaching that can be replicated or adapted in other institutions. Each contributor responds to fundamental questions at the core of any translation course -- for example, how is translation defined? What qualifies students for admission to the course? What impact does the institutional site have upon the course or pedagogy? Teaching Translation will be relevant for all those working and teaching in the areas of translation and translation studies.--Publisher website